The Western Other In The Novel Of The Young Bedouin By Maqbool Al-Alawi - Al Khadari, Nasser Bin Mubarak (Ijaz Arabi Journal of Arabic Learning, 2024)
This study is concerned with analyzing the image of the other in literary texts where the people and cultures meet. This literary genre is considered one of the most critical areas of comparative literature studies in modern criticism. The study aims to prepare the students for comparative studies, one of the most essential domains that can benefit language learners. It enables the students to become familiar with and hold contrastive studies between Arabic as their mother tongue and the other languages and increase their linguistic proficiency. In addition, access to such studies or the experience of conducting them develops the learner's skills and abilities to understand, analyze, and track intellectual and reading coherence. Comparative literary studies have recently turned towards the novel to examine the image of nations and people in the writings of some of them in this literary genre. The narrative specificity of this genre is considered very important, as are people and cultures and the multiplicity of relationships of effect and influence among one another. From the importance of this standpoint comes the idea of this research, which seeks to Study the image of the Western Other in the novel "Albadawi Alsaqeer" (The Young Bedouin) by the Saudi novelist Maqbool Al-Alawi. This is due to its heavy reliance in its structure on the "Western Other" in its various manifestations and dimensions. They consider it looked at this other with a neutral and balanced vision that differed from the prevailing fictional writings that dealt with the relationship between the East and the West.